Laboratory measurements of the optical properties of sea salt aerosol - Irshad, R; Grainger, D; Peters, D; McPheat, R; Smith, K; Thomas, G (Copernicus Publications, 2008)
The extinction spectra of laboratory generated sea salt aerosols have been measured from 1μm to 20μm using a Bruker 66v/S FTIR spectrometer. Concomitant measurements include temperature, pressure, relative humidity and the aerosol size distribution. The refractive indices of the sea salt have been determined using a simple harmonic oscillator band model (Thomas et al., 2004) for aerosol with relative humidities between 0.1% to 100% sea salt. The resulting refractive index spectra show significant discepancies when compared to existing sea salt refractive indices.